OP0050 Evolution of the alternative classification of HLA-DRB1 alleles in rheumatoid arthritis: Impact on the production of the anti-citrullinated protein antibodies and structural progression, data from the ESPOIR cohort. (23rd January 2014) - Ruyssen-Witrand, A.; Gourraud, P.-A.; Nigon, D.; Lukas, C.; Miceli-Richard, C.; Jamard, B.; Cantagrel, A.; Cambon-Thomsen, A.; Dieudé, P.; Constantin, A.
Abstract : Background: HLA-DR shared epitope alleles have been previously reclassified in an alternative classification (1) relevant in terms of rheumatoid arthritis (RA) susceptibility, ACPA production and severity. However, subclassification of S2 alleles according to the amino acid at position 70 has never been assessed. Objectives: The aim of this work was to validate a modified version of this alternative classification in terms of association with ACPAs production and radiographic progression in a cohort of early RA. We proposed to devise S2 groups into 2 groups (S2D and S2P) according to the amino acid at position 70 and to pool the different alleles in 3 risk groups. Methods: 612 patients included in the ESPOIR cohort, fulfilling ACR/EULAR 2009 criteria for RA were genotyped for HLA-DRB1 alleles. Radiographs were centrally read and scored using the Total Sharp/van der Heijde Score (mTSS). The different alleles were classified according to a modified version of the alternative classification (X, S1, S2D, S2P, S3D, S3P) and were pooled according to ACPA production risk: the "L group" for low risk (S1 and X), the "N group" for neutral risk (S2D and S3D), "H group" for high risk (S3P and S2P). The association between the different genotypes and 1) the ACPA positivity was assessed by a Chi square test, 2) the radiographic progression at 12 months by Wilcoxon's rank sum test. Finally, a logistic regression was used to assess the risk of progression (≥1 mTSS unit). Results: The LH, NH and HH genotypes were significantly associated with ACPA positivity (respectively OR[95%CI]=1.92 [1.34-2.75], p=0.0002, OR[95%CI]=1.84 [1.02-3.37], p=0.03, OR[95%CI]=4.83 [2.66-9.20], p<0.0001), whereas LL genotype had a protective effect (OR[95%CI]=0.18 [0.11-0.28], p<0.0001). LH and HH genotypes were associated with structural progression (respectively p=0.0067 and p<0.0001) whereas LL and LN genotypes seemed to have a protective effect on progression (respectively p<0.0001 and p=0.0151). H allele carriage was significantly associated with progression in the multivariate model independently of ACPA status (OR [95%CI]=1.90 [1.08-3.35], p=0.026). Conclusions: Pooling alleles in 3 risk groups simplify the alternative classification of HLA-DRB1 alleles and is relevant in terms of association with ACPA production and radiographic progression. References: du Montcel ST, Michou L, Petit-Teixeira E, Osorio J, Lemaire I, Lasbleiz S, Pierlot C, Quillet P, Bardin T, Prum B, et al: New classification of HLA-DRB1 alleles supports the shared epitope hypothesis of rheumatoid arthritis susceptibility. Arthritis Rheum 2005, 52:1063-1068. Disclosure of Interest: None Declared